Changes In Sociocultural Representations In Popular Digital Games - Göksu, İdris; Aslan, Alper; Karakuş, Türkan (The Turkish Online Journal of Design Art and Communication, 2016)
The aim of this study is to investigate digital games with respect to sociocultural aspects and examine whether they are influenced by social and cultural events. In total, 14 digital games were studied by the researchers through documentation analysis. Results showed that sociocultural factors and current events were heavily featured in games from 2002-2004, while 2012-2014 games highlighted social interaction, natural environments of the world, and exceptional, action-packed events. This study is valuable for revealing how games reflect sociocultural changes over time.
Keywords: Digital games; socio-cultural issues; content analysis; game scenario; popular games; Dijital oyunlar; sosyokültürel unsurlar; içerik analizi; oyun senaryosu; popüler oyunlar